GAMBARAN PENGETAHUAN PASIEN TENTANG DIET PADA PENYAKIT JANTUNG DI POLI JANTUNGRSUD ARIFIN ACHMAD PROVINSI RIAU - Roza, Andalia; Ilham, Muhamad (PROGRAM STUDI DIII KEPERAWATAN UNIVERSITAS ABDURRAB PEKANBARU, 2017)
Abstract, The heart is an organ that is composed of strong muscles and pump blood that carries oxygen throughout the body and bring food. Heart Diet is very important because heart disease is caused by faulty lifestyle and the lifestyle of one of them is nutrition. The purpose of this study to describe patients knowledge about diet on cardiovascular disease in poly heart Arifin Achmad Hospital Riau Province in 2015. The design of this type of research is descriptive quantitative research, which means outlining the current phenomenon of problem situations somewhere. The research sample included 30 people using accidental sampling technique. This research was conducted from 28 November 2015-18 December 2016. The data was collected by questionnaire. Results of the study were obtained from 30 respondents have good knowledge of 20 people (6.66%), Just 5 votes (16.67%), Less than 23 people (76.67%). From the results of this study concluded that knowledge of a patient in cardiac poly Arifin Achmad Hospital Riau province less knowledgeable. Given this research is expected to patients in order to improve the application of a healthy lifestyle in order to be solusu the right to live a healthy life. Keywords         : Knowledge, Diet, Heart References       : 25 books(2009-2015